2020
DOI: 10.3847/1538-4357/abcafe
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Chromospheric Spicules in Magnetic Bright Points: An Analytical Approach Using Cartesian Slab Geometry

Abstract: We aim to provide insight into chromospheric spicules by suggesting a new formation mechanism. A magnetic field boundary condition is imposed, generating an Alfvén wave that shears a magnetic slab and propagates up the slab. The resulting Lorentz force accelerates material vertically, potentially nonlinearly driving a jet-like feature. This formation mechanism is applied to take place in a magnetic bright point embedded in the photosphere, providing motivation to use the simplifying assumption of a zero-β plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The mass flow along the propagation direction of the switchback is due to the vertical component of the velocity perturbation, and not due to magnetic pressure gradients, as in the case of ponderomotive forces (Hollweg 1971;Chen & Hasegawa 1974), the magnetic field magnitude being constant. Nevertheless, the discussion above on gravitational damping should apply also for non-circularly polarized waves which lift mass ponderomotively (e.g., Oxley et al 2020). While ponderomotive forces are present irrespective of gravitational stratification, in the case of the propagating Alfvénic switchback there are essentially no density perturbations without gravity.…”
Section: Resultsmentioning
confidence: 99%
“…The mass flow along the propagation direction of the switchback is due to the vertical component of the velocity perturbation, and not due to magnetic pressure gradients, as in the case of ponderomotive forces (Hollweg 1971;Chen & Hasegawa 1974), the magnetic field magnitude being constant. Nevertheless, the discussion above on gravitational damping should apply also for non-circularly polarized waves which lift mass ponderomotively (e.g., Oxley et al 2020). While ponderomotive forces are present irrespective of gravitational stratification, in the case of the propagating Alfvénic switchback there are essentially no density perturbations without gravity.…”
Section: Resultsmentioning
confidence: 99%
“…Kudoh & Shibata (1999) have also studied the evolution of spicules due to Alfvén waves. Oxley et al (2020) provide the analytical model for the generation of spicule-like jets due to the tension component of the Lorentz force. Nishizuka et al (2008) have given the physical scenario of the formation of longer chromospheric jets due to Lorentz force and Alfvén perturbations at their base.…”
Section: Discussionmentioning
confidence: 99%
“…There has been no conclusive explanation of the spicules since their discoveries in 1877. Many models have been proposed based on the source of energy driving the ejection of spicules from the chromosphere [10], including the strong pulse model [11,12], the rebound shock model [13], the Alfv en wave model [14][15][16][17][18][19][20] and the magnetic reconnection model [9,21]. Dey et al discussed the similarities between spicules observed on the Sun and jets produced by polymeric fluids.…”
Section: Introductionmentioning
confidence: 99%